Role and sources of protein in the nutrition of young children - E.A. Pyr'eva; A.I. Safronova; E.A. Netunaeva; M.I. Timoshina (LCC «Medicine-Inform», 2021)
E.A. Pyr'eva, A.I. Safronova, E.A. Netunaeva, M.I. Timoshina Federal Research Center for Nutrition & Biotechnology, Moscow, Russian Federation This paper discusses the introduction of complementary feeding considering the novel data on its role in ensuring the health and development of a child. One of the most controversial issues is protein intake that significantly changes both quantitatively and qualitatively after introducing supplementary food. Excessive protein intake is associated with metabolic load and growth acceleration that is considered the predictor of  overweight and obesity, metabolic syndrome and diabetes. The importance of meat puree in the first year of life (also from the perspective of optimizing nutrition to achieve adequate zinc and iron levels) is highlighted. Domestic and international studies on the effects of proteins of various origins (meat, milk, etc.) on growth and the risk of obesity are addressed. The importance of qualitative rather than quantitative composition of consumed protein is emphasized. Keywords: young children, supplementary food, protein, meat, growth, insulin-like  growth factor. For citation: Pyr'eva E.A., Safronova A.I., Netunaeva E.A., Timoshina M.I. Role and sources of protein in the nutrition of young children. Russian Journal of Woman and Child Health. 2021;4(1):65-69. DOI: 10.32364/2618-8430-2021-4-1-65-69.